Pendidikan Agama Multiperspektif sebagai Kerangka Kurikulum untuk Menumbuhkan Toleransi di Sekolah Dasar Negri 01 Kawengen, Semarang, Indonesia: Studi Kasus Kualitatif - Madani, Siti Ulfia; Nur Latifah, Umu; Musfiroh, Musfiroh (IAI Darussalam, 2026)
Abstract This study discusses the application of multi-perspective religious education and its contribution in shaping religious tolerance attitudes in students at SDN 01 Kawengen . This research is motivated by intolerant acts, bullying, and satirical religious attitudes, even appearing at the basic education level. Although this phase is important in shaping the character and social interaction of students in a heterogeneous society. This research was conducted with a qualitative approach using a single case study method. Data collection was carried out by means of in-depth interviews, direct observations, and document studies, involving school principals, religious teachers, and students with diverse religious backgrounds. Data analysis uses an interactive method consisting of data simplification, data presentation, and conclusion drawn, reinforced by triangulation to ensure the reliability of the results. The results of the study show that multiperspective religious education is applied through religious learning according to their respective beliefs, an inclusive learning approach, exemplary examples from educators, the application of tolerance values in theme learning, and school habituation programs such as JEMPOLAN. This implementation helps to increase mutual respect and strengthen cooperation between students. Supporting factors include the diversity of the school environment, cooperation between teachers and parents, and a school culture that emphasizes togetherness, while limitations in interfaith dialogue are major obstacles. Keywords: multiperspective religious education, religious tolerance, primary school, religious moderation Abstrak Penelitian ini membahas penerapan pendidikan agama multiperspektif serta kontribusinya dalam membentuk sikap toleransi beragama pada siswa di SDN 01 Kawengen . Penelitian ini dilatarbelakangi oleh adanya tindakan intoleran, perundungan, serta sikap keagamaan yang menyendikan, bahkan muncul di tingkat pendidikan dasar. Meskipun fase ini penting dalam membentuk karakter dan interaksi sosial siswa dalam masyarakat yang heterogen. Penelitian ini dilakukan dengan pendekatan kualitatif menggunakan metode studi kasus tunggal. Pengumpulan data dilakukan dengan cara wawancara mendalam, observasi langsung, serta studi dokumen, dengan melibatkan kepala sekolah, guru agama, serta siswa yang memiliki latar belakang agama beragam. Analisis data menggunakan metode interaktif yang terdiri dari penyederhanaan data, penyajian data, serta penarikan kesimpulan, diperkuat oleh triangulasi untuk memastikan keandalan hasil. Hasil penelitian menunjukkan bahwa pendidikan agama multiperspektif diterapkan melalui pembelajaran agama sesuai keyakinan masing-masing, pendekatan pembelajaran yang inklusif, contoh teladan dari pendidik, penerapan nilai toleransi dalam pembelajaran tema, serta program pembiasaan sekolah seperti JEMPOLAN. Penerapan ini membantu meningkatkan sikap saling menghormati dan memperkuat kerja sama antar siswa. Faktor yang mendukung termasuk keberagaman lingkungan sekolah, kerja sama antara guru dan orang tua, serta budaya sekolah yang menekankan kebersamaan, sementara keterbatasan dalam dialog antaragama menjadi hambatan utama. Kata kunci: pendidikan agama multiperspektif, toleransi beragama, sekolah dasar, moderasi beragama.